Submicroscopic changes of secretory cardiomyocytes in the early postcompression period of crush syndrome - Yuryk , Ya.I.; Kuziv , O.E.; Yuryk , I.I. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. Crush syndrome is manifested by the activation of the pituitary-hypothalamic-adrenal system, what is confirmed by a significant increase in the blood levels of catecholamines, cortisol and corticosterone. Its antagonist is the atrial natriuretic peptide, which is synthesized by the myoendocrine cells of the heart, but the question of its participation in the implementation of the adaptation syndrome under the conditions of the postcompression period of crush syndrome remains unresolved. Objective: to establish submicroscopic changes atrial myoendocrynocytes in the early postcompression period of crush syndrome. Methods. The study was conducted on 24 white male laboratory rats weighing 240–270 grams. The experimental group consisted of 16 animals, divided into 2 to 8 animals each, which were removed from the experiment after 1 and 3 days. The control group included 8 intact male rats. Crush syndrome was simulated by compression the soft tissues of the thigh of the right pelvic extremity. Analgesia was performed by intraperitoneal injection of ketamine hydrochloride (100 mg/kg of body weight), the compression force was 7 kg/cm2, the area of the compressive surface – 5 cm2 for 6 hours. The withdrawal of experimental animals from the experiment was performed by bloodletting after intraperitoneal injection of sodium thiopental. Ultrathin tissue sections of the right and left auricles of the heart were studied using a PEM – 125 K electron microscope. Results. 1 day after decompression a submicroscopic examination of the auricles of the heart revealed a significant increase the number of secretory granules, among which mature and diffusing types predominated, which were localized in large groups in the paranuclear zone, as well as between mitochondria, myofibrils and near the endotheliocytes of hemocapilaries. After 3 days of the study destructive changes in the nuclei, energy, contractile and secretory apparatuses of myoendocrinocytes, young and diffusing secretory granules were rarely found. Conclusion. In the early postcompression period of crush syndrome 1 day after decompression hyperplasia of mature and diffusing secretory granules occurs in the myoendocrinocytes of the auricles of experimental rats, which is a morphological manifestation of the accumulation and secretion of atrial natriuretic peptide and significant decrease the number of secretory granules, alterative changes in the myoendocrinocytes of the heart after 3 days of the study, which indicates suppression endocrine function of the heart.